The Prosecutor as a Final Safeguard Against False Convictions: How Prosecutors Assist with Exoneration - Webster, Elizabeth (2020)
Prosecutors have helped secure an unprecedented number of recent exonerations. This development, combined with the rapid emergence of district attorney-initiated conviction integrity units (CIUs) raises several questions. How do prosecutors’ offices review postconviction innocence claims? How do they make decisions about the merits of those claims? How do CIU processes differ from non-CIU processes? This study examines the circumstances surrounding prosecutor-assisted exoneration cases through semi-structured interviews with 20 prosecutors and 19 defense attorneys. It draws from a sample of both CIU and non-CIU prosecutors, thereby enabling comparisons. Respondents were asked about their experiences and decision-making structures in specific, post-2005 exoneration cases as well as their impressions of postconviction practices more broadly. Their responses revealed the salience of office hierarchies and appellate principles for prosecutors’ postconviction discretion. Unlike earlier stages—such as charging and plea bargaining—few decisions appear to be delegated to the line prosecutor in the postconviction stage. Therefore, I incorporate organizational accident theory to understand key decisions, such as which prosecutor should be tasked with reviewing innocence claims, how to screen claims, and how to decide the outcome of an innocence claim. I find that prosecutors work within a system that emphasizes procedural errors over factual ones and that allows for a narrow and belated discovery of false convictions. Thus, prosecutors’ postconviction efforts do not appear likely to create a new pathway to exoneration for pro se defendants, or to identify false convictions that have not already been discovered by trusted defense attorneys, innocence organizations, and/or journalists. Although most prosecutors described processes that could reliably facilitate unbiased case review and reinvestigation, these processes were reserved for only the most extraordinary of innocence claims. The significance of this research for policy (in the crafting of legislation and court rules) and practice (in the processing of innocence claims through prosecutors’ offices) is discussed